Advanced neutral gas diagnostics for magnetic confinement devices. (7th September 2017) - Wenzel, U.; Kremeyer, T.; Schlisio, G.; Marquardt, M.; Pedersen, T.S.; Schmitz, O.; Mackie, B.; Maisano-Brown, J.; team, the W7-X
Abstract: For the study of particle exhaust in nuclear fusion devices the neutral pressure must be measured in strong magnetic fields. We describe as an example the neutral pressure gauges in the Wendelstein 7-X stellarator. Two types are used: hot cathode ionization gauges (or ASDEX pressure gauges) and Penning gauges. We show some results from the first experimental campaign. The main problems were runtime effects and the failure of some ASDEX pressure gauges. To improve the reliability we integrated a new LaB 6 electron emitter into the ASDEX pressure gauges. In addition, a special Penning gauge without permanent magnets was developed in order to operate Penning gauges near the plasma edge. These new pressure gauges will be used in the upcoming campaign of Wendelstein 7-X.